Outcomes of type III tympanoplasty: our experience - Chandrashekhar, Ravishankar; Bandadka, Ramya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Type III tympanoplasty involves complete disease clearance from middle ear cleft and retaining or improving the serviceable hearing by ossiculoplasty. Various auto and allografts have been used with variable outcomes. The objective of the study was to evaluate hearing improvement and healing of cavity in patients who underwent type III tympanoplasty. Methods: A retrospective chart review of 21 patients who underwent type III tympanoplasty at Bowring and Lady Curzon Hospital from January 2018 to December 2018 was done. In 7 patients autologous incus, 6 tragal cartilage and 8 teflon prosthesis was used for ossiculoplasty. Intra and postoperative events were assessed. Pure tone audiograms done after 3 and 6 months were compared. Results: 15 patients who underwent canal wall down procedure (CWDP) had a mean hearing gain of 20.33 dB and 26.67 dB while in 5 patients of canal wall up procedure (CWUP) group mean hearing gain was 22.5 dB and 27.5 dB at 3 and 6 months after surgery respectively. Hearing gain was similar in both groups irrespective of the prosthesis used. Autologous materials were used in most of the CWUP with intact stapes and teflon prosthesis was used in majority of CWDP where only mobile stapes foot plate was present. Prosthesis extrusion was not encountered in any of our cases so far in this series. Conclusions: The post-operative hearing gain with autologous incus, tragal cartilage and teflon middle ear prosthesis are similar. Teflon prosthesis is an effective material for ossiculoplasty, especially useful when incus and stapes are absent while autologous incus or tragal cartilage are preferred in cases with intact stapes head.